Analisis Penggunaan Bahasa Indonesia Baku dalam Praktik Micro Teaching Mahasiswa STKIP Sinar Pancasila Betun - Maria S. P. Nahak; Maria R. Asa; Pingki P. Soi; Yeni E. Klau; Maria O.L. Leki; Finsensius R. N. Fahik; Damian Puling; Fransiskus P. Dewa (Journal Innovation In Education, 2025)
This study aims to analyze the use of standard Indonesian language in microteaching practices by students of STKIP Sinar Pancasila Betun. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results show that most students are not yet consistent in using standard language during their microteaching sessions. The primary influencing factors are the strong influence of regional language backgrounds and the lack of intensive language training from supervising lecturers. This study recommends that educational institutions provide targeted coaching and continuous assessment regarding the use of standard Indonesian in the learning process.